2010
DOI: 10.5012/jkcs.2010.54.5.582
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of 1-Benzofuran-2-yl thiadiazoles, Triazoles and Oxadiazoles by Conventional and Non-conventional Methods

Abstract: ABSTRACT. The synthesis of benzofuran based 1,3,4-thiadiazoles, 1,3,4-triazoles and 1,3,4-oxadiazole via cyclocondensation of thiosemicarbazides have been carried out by conventional and non-conventional methods in excellent yields of product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The Schiff bases (L 1 ) – (L 3 ) possessed the characteristic azomethine (HC=N) stretching [17] at 1632–1638 cm −1 , hence giving clue of condensation product. The ligand (L 1 ) showed the bands at 1090 cm −1 due to (C–O) vibrations [18]. The comparison of the IR spectra of the Schiff bases (L 1 ) – (L 3 ) with their metal(II) complexes (1) – (12) indicated that the Schiff bases were principally coordinated to the metal(II) ions bidentately.…”
Section: Resultsmentioning
confidence: 99%
“…The Schiff bases (L 1 ) – (L 3 ) possessed the characteristic azomethine (HC=N) stretching [17] at 1632–1638 cm −1 , hence giving clue of condensation product. The ligand (L 1 ) showed the bands at 1090 cm −1 due to (C–O) vibrations [18]. The comparison of the IR spectra of the Schiff bases (L 1 ) – (L 3 ) with their metal(II) complexes (1) – (12) indicated that the Schiff bases were principally coordinated to the metal(II) ions bidentately.…”
Section: Resultsmentioning
confidence: 99%